Comparison of Denver and Leeds laboratory flotation cells: Effect of particle size and hydrodynamics - M. P. Tshazi; L. S. Leal Filho; N. Naude (The Southern African Institute of Mining and Metallurgy, 2025)
In this paper, the authors performed experiments in the Denver and Leeds laboratory flotation devices at the University of Pretoria at various particle sizes to evaluate the performance of the devices. Quartz was used in a single mineral system at discrete sizes fractions, -25 μm, +25- 45 μm, +45-75 μm, and +75-106 μm. Hydrodynamic analysis, based on dimensionless power and Reynolds numbers, indicated that the Leeds cell required higher power input to achieve comparable flow conditions. Specifically, the Leeds cell exhibited an average power number of 1.03, whereas the Denver cell averaged 0.77 within the same impeller speed range of 1000 rpm–1500 rpm. For comparative flotation performance, impeller speeds were calibrated, resulting in operating speeds of 1200 rpm for the Denver cell and 1400 rpm for the Leeds cell. The cells performed similarly at two coarser-sized fractions. However, some deviations were observed in the finer particle size range. The -25 μm (fine) fraction initially achieved a recovery of only 15%. An additional reagent dosage was required to enhance the recovery of this fraction significantly. These findings highlighted the influence of particle size on flotation recovery. For all experiments, the Denver laboratory flotation cell outperformed (defined by higher recovery) the Leeds device, while still operating at a lower impeller speed. This advantage can be attributed to its impeller-stator design and air dispersion features, effectively overcoming slurry resistance and resulting in superior flotation performance compared to the Leeds cell.